THE IMPACT OF BUSINESS PROCESS MANAGEMENT ON ORGANIZATIONAL STRATEGY - Vlad BĂLĂNESCU; Paul SOARE; Vlad BELICIU; Cristina ALPOPI (Business Excellence and Management, 2013)
In this paper I attempted to establish a link between business process management and strategic management. After the introduction, in the second chapter I made a short presentation of business process and business process management, what the concept entails and prospects. The third chapter contains a definition of strategic management and some key issues of this concept that are pertinent in relation to business process management. Finally, the fourth chapter focuses of the impact that business process management has on organizational strategy as a whole and on its components.